Synchronization: Stability and duration time - Woafo, P.; Kraenkel, Roberto André [UNESP] (Amer Physical Soc, 2002)
We consider the problem of stability and duration of the synchronization process between self-excited oscillators, both in their regular and chaotic states. Making use of the properties of Hill equation describing the deviation between the slave and the master, we derive the stability conditions and expressions of the synchronization time. A fairly good agreement is obtained between the analytical and numerical results.